2010
DOI: 10.1176/appi.ajp.2009.09060881
|View full text |Cite
|
Sign up to set email alerts
|

Association of Western and Traditional Diets With Depression and Anxiety in Women

Abstract: These results demonstrate an association between habitual diet quality and the high-prevalence mental disorders, although reverse causality and confounding cannot be ruled out as explanations. Further prospective studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

45
492
6
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 613 publications
(583 citation statements)
references
References 37 publications
45
492
6
8
Order By: Relevance
“…For example in a study on women 20-93 years no association was found between consumption of a Mediterranean-type diet, containing fruit, salads, fi sh, tofu, beans, nuts, yogurt, and red wine, and anxiety (JACKA et al, 2010). The reason of discrepancy in the results of studies could be the cohort or cross-sectional nature of the studies, difference in the method of assessing psychological disorders, difference in study population (one sex or both, educational level, healthy subjects or patients), the use of principal component analysis for extraction of dietary patterns, difference in statistical methods, and the type of covariates used.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example in a study on women 20-93 years no association was found between consumption of a Mediterranean-type diet, containing fruit, salads, fi sh, tofu, beans, nuts, yogurt, and red wine, and anxiety (JACKA et al, 2010). The reason of discrepancy in the results of studies could be the cohort or cross-sectional nature of the studies, difference in the method of assessing psychological disorders, difference in study population (one sex or both, educational level, healthy subjects or patients), the use of principal component analysis for extraction of dietary patterns, difference in statistical methods, and the type of covariates used.…”
Section: Resultsmentioning
confidence: 98%
“…For example, a lower consumption of fruit was associated with higher scores of perceived stress in a cross-sectional study on college students (LIU et al, 2007). Likewise, a traditional healthy dietary pattern characterized by vegetables, fruit, meat, fi sh, and whole grains was associated with lower odds for anxiety disorders in a cross-sectional study of women aged 20-93 years in Australia (JACKA et al, 2010). Antioxidants and polyphenols in fruit of the Mediterranean-type dietary pattern may be effi cacious in prevention of anxiety (BOUAYED, 2010).…”
Section: Resultsmentioning
confidence: 98%
“…In recent years, dietary patterns have been the subject of increased attention in the field of adolescent mental health. Researchers noticed that inadequate nutrition and poor diet quality (fast food, confectionery items, animal foods) are more frequently associated with mental problems (10)(11)(12)(13)(14)(15) . A cross-sectional relationship between diet quality and depression was verified in a large sample of adolescents from a diverse range of sociodemographic backgrounds (13) .…”
mentioning
confidence: 99%
“…An unhealthy dietary pattern has been associated with poor mental health in both adults [6,7], children and adolescents [8], even though the precise mechanisms are unclear [9]. A general concern is given to the effects of the typically modern Western dietary pattern, which is characterized by high levels of meat and saturated fat and low levels of fish and vegetables [10].…”
Section: Introductionmentioning
confidence: 99%